2020
DOI: 10.3390/su12176701
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Development Goals (SDGs): Assessing the Contribution of Higher Education Programmes

Abstract: Universities are engines of societal transformation and can nurture future citizens and navigate them towards sustainability through their educational programmes. Here, we developed an assessment framework for educational institutions to evaluate the contribution of their educational programmes to sustainability by reviewing the alignment of their intended learning outcomes to the enabling conditions for a vision of sustainability based on the Sustainable Development Goals (SDGs). The tool is based on a system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(76 citation statements)
references
References 36 publications
0
43
0
1
Order By: Relevance
“…Universities play a key role in providing education that goes in accordance with sustainable development. In this regard, Kioupi and Voulvoulis [108] developed a framework to assess the alignment of 40 UK and European master's programs (related to environment and sustainability) to the SDGs. They reported the lack of some aspects (i.e., health, well-being, among others) within these educational programs and highlighted that universities must be aware of their contribution to sustainable development.…”
Section: Scientific Communitymentioning
confidence: 99%
“…Universities play a key role in providing education that goes in accordance with sustainable development. In this regard, Kioupi and Voulvoulis [108] developed a framework to assess the alignment of 40 UK and European master's programs (related to environment and sustainability) to the SDGs. They reported the lack of some aspects (i.e., health, well-being, among others) within these educational programs and highlighted that universities must be aware of their contribution to sustainable development.…”
Section: Scientific Communitymentioning
confidence: 99%
“…In a highly globalized education system, internationalization is a prerequisite for the sustainable development of higher education institutions; recruiting qualified international students and maintaining a good relationship with them are necessary [61]. This approach directly corresponds to the attributes of diversity and inclusion, focusing on international and intercultural interactions and interdependence, which are addressed in the Sustainable Development Goals (SDGs) of higher education programs [18]. We believe that this study provides educational institutions with a useful guideline for building and maintaining mutually beneficial relationships with international students.…”
Section: Discussionmentioning
confidence: 99%
“…Universities are expected to offer sustainable education in the rapidly changing era of the Fourth Industrial Revolution. Indeed, higher education institutions play a critical role in societal transformation toward sustainability through their leadership and curricula [13]. Universities help society develop by preparing graduates to acquire knowledge and skills required by companies.…”
Section: Sustainability In Higher Educationmentioning
confidence: 99%
“…Spencer and Spencer (1993) suggested that competency is a potential characteristic of individuals who perform effectively according to specific criteria in any task or situation [19] (pp. [11][12][13][14][15]. Parry (1996) and Lee (2002) viewed competency as a collection of knowledge, skills, and attitudes that can aid performance [20] (p. 50), [21] (pp.…”
Section: Competency For the Sustainability In Higher Educationmentioning
confidence: 99%